The Mutualism Interactions in the Changes of Social and Islamic Law - Ade Dedi Rohayana (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
Humans and everything of God's creation will benefit from Islamic law. Through the establishment of beneficial rules, Islam seeks to advance the world and its inhabitants. Islamic law must contain advantages throughout history. Changes in the law and disagreements in the law that arise among Islamic jurists are all advantageous. Change is an essential component of human existence. This is due to the fact that God has provided humanity with a great deal of capacity to effect significant life changes. God endowed people with three potentials: the potential for rationality or intellectual capacity, defensive potential, and offensive potential. These three potentials are the driving force and urge for humans to be able to differentiate between useful and harmful activities. Individually and socially, therefore, human life is highly dynamic, continually evolving, and ever-changing. These transformations and processes are known as social change in society. Islamic law must be revised due to the inevitability of societal development. Islamic law, as God's rule that benefits humanity, is unquestionably capable of adapting to and responding to this societal transformation. In order to respond and adapt to these societal changes, Islamic jurists (fuqaha) created a widely accepted norm, namely, that Islamic law can alter and vary based on changes in time, location, circumstances, intents, and traditions. Social changes have ramifications for the evolution of Islamic law, while the evolution of Islamic law has implications for social change. The interaction between the two is mutualistic.